2020
DOI: 10.3390/cells9112342
|View full text |Cite
|
Sign up to set email alerts
|

The PTEN Conundrum: How to Target PTEN-Deficient Prostate Cancer

Abstract: Loss of the tumor suppressor phosphatase and tensin homologue deleted on chromosome 10 (PTEN), which negatively regulates the PI3K–AKT–mTOR pathway, is strongly linked to advanced prostate cancer progression and poor clinical outcome. Accordingly, several therapeutic approaches are currently being explored to combat PTEN-deficient tumors. These include classical inhibition of the PI3K–AKT–mTOR signaling network, as well as new approaches that restore PTEN function, or target PTEN regulation of chromosome stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 393 publications
(515 reference statements)
0
37
0
1
Order By: Relevance
“…PCa is characterized by an activation of the PI3K-AKT-mTOR (phosphatidylinositol-3-kinase [PI3K], protein kinase B [PKB/AKT], and mTOR) pathway [ 131 ] and deficiency of PTEN (phosphatase and tensin homolog deleted on chromosome 10), a tumor suppressor gene that inhibits the PI3K-AKT-mTOR pathway, is associated with PCa [ 132 ]. Metformin is an AMPK activator and induces PTEN [ 133 ].…”
Section: Prostate-related Healthmentioning
confidence: 99%
“…PCa is characterized by an activation of the PI3K-AKT-mTOR (phosphatidylinositol-3-kinase [PI3K], protein kinase B [PKB/AKT], and mTOR) pathway [ 131 ] and deficiency of PTEN (phosphatase and tensin homolog deleted on chromosome 10), a tumor suppressor gene that inhibits the PI3K-AKT-mTOR pathway, is associated with PCa [ 132 ]. Metformin is an AMPK activator and induces PTEN [ 133 ].…”
Section: Prostate-related Healthmentioning
confidence: 99%
“…This is in accordance with previous studies, showing that after HT treatment for 24 h, the cytotoxic effect depended on the Phosphate Tensin homolog ( PTEN ) status of the cell line [ 40 ]. PTEN is considered a tumor suppressor gene that is commonly mutated or deleted in PCa patients, leading to a functional loss, which is related with higher aggressiveness of the disease and a poorer clinical outcome [ 41 ]. In this sense, we observed that PTEN -null LNCaP and PC-3 cells (−/−) were most resistant, whereas the 22Rv1 cells (+/+) were the most sensitive.…”
Section: Resultsmentioning
confidence: 99%
“…Oncogenic activation of the phosphatidylinositol-3-kinase (PI3K)-AKT (protein kinase B)-mammalian target of rapamycin complex 1 (mTORC1) pathway is a frequent finding in PCa that promotes tumorigenesis, tumor progression, and resistance to therapy [22,23] . PI3K-AKT-mTORC1 signaling is elevated in a high proportion of PCa and castration-resistant PCa (CRPC) [24][25][26][27] . Reduced expression of phosphatase and tensin homolog deleted on chromosome 10 (PTEN), a critical tumor suppressor of PCa, correlates with PCa progression and poor prognosis [28] .…”
Section: Genetic Deviations Activating Pi3k-akt-mtorc1 In Pcamentioning
confidence: 99%
“…Milk consumption has been related to several common mTORC1-driven cancers of Western civilization, especially PCa [166][167][168][169][170][171][172][173][174][175] , breast cancer [176][177][178][179][180][181][182][183] , hepatocellular carcinoma [184][185][186][187] , and diffuse large B-cell lymphoma [188] . Notably, overactivated mTORC1 signaling is a common hallmark of PCa [21,22,27,[57][58][59][60][61] , breast cancer [189][190][191][192][193][194] , hepatocellular carcinoma [195][196][197][198][199][200] , and diffuse large B-cell lymphoma [201][202][203][204] . Based on a recent review of the literature, Vasconcelos et al [154] confirmed a possible relationship between milk consumption and mTORC1-...…”
Section: Calcium-independent Milk-induced Mtorc1 Activationmentioning
confidence: 99%